ANALYSIS AND OPTIMIZATION ON SMOOTH ROAD SHAKE PROBLEM OF STEERING WHEEL FOR A COMMERCIAL VEHICLE - XU ShouFu; SUN Tao; SONG GuiXia; SHI YongJin; ZHENG SongLin (Jixie qiangdu)
In order to investigate the problem that steering wheel shake of a commercial vehicle at high speed,the approach of theory analysis combined with the road test is used to find out that the wheel is the cause of the steering wheel shake excitation source and transfer path of vibration is verified. Time domain and frequency domain analysis are carried out for response signals from all the measuring points which are arranged in the road test,and discovery the smooth road shake is most intense at the speed of 90km/h. Key component of the steering system in transfer path is optimized to cope with the problem of energy absorption in the process of steering wheel shake at high speed. Sensitivity analysis on the bushing stiffness of low control arm in a validated model for vehicle dynamics is carried out by using Adams/Insight in the downstream subsystem. Sensitivity analysis result shows that bushing stiffness X of low control arms,which has a greater impact on the target point. The phenomenon of steering wheel shake at high speed has been significantly improved after the simulation analysis and test validation.